Divertor Development for a Future Fusion Power Plant - Norajitra, Prachai (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2011)
Nuclear fusion is considered as a future source of sustainable energy supply. Since the H-mode discovery in ASDEX experiment ""Divertor I"" in 1982, the divertor has been an integral part of all modern tokamaks and stellarators. The major goal of this thesis is to develop a feasible divertor design for a fusion power plant to be built after ITER. The thesis describes the approach in the conceptual development of a helium-cooled divertor and the methods of verification and validation of the design.